The Cultivation of Valdivia gayana J. RÉMY.: a Little Known Herb from Southern Chile - Hughes, Kate; Ensoll, Andrew; Gardner, Martin F. (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2014)
Valdivia gayana J. Rémy. is a herbaceous, sometimes sub-shrubby member of Escalloniaceae, a family dominated by woody species. It has a limited distribution in southern Chile and, to the knowledge of the authors, has not been cultivated in gardens outside Chile before. It is an unusual species in many senses and the collection and cultivation from seed at the Royal Botanic Garden Edinburgh is described here and suggestions for propagating the plant from cuttings are made.